An investigation into the bimodal flutter details based on flutter derivatives' contribution along the bridge deck's surface. Issue 192 (September 2019) - Li, K.; Li, S.; Ge, Y.; Yan, B.
Abstract: Flutter derivatives are commonly used to describe the behavior of the self-excited force. Based on them, most existing analyzing methods can reveal the overall process of the flutter evolution very well but are not so good at describing the internal mechanism combining with the aerodynamic pressure. To quantify the contributions from each zone of the deck's surface, a novel definition of Surface-Flutter-Derivatives (SFDs) are introduced. The wind-induced changes of the mode characteristics are allocated to different parts of the deck's surface, with the help of further derivations based on Chen's bimodal flutter stability expressions. Verification of the derived formulas are carried using the Computational-Fluid-Dynamics (CFD) method, based on deck shape and dynamic characteristics of the Great Belt Bridge. Next, the SFD's advantages in exploring the weights of the self-excited force's components and investigating the stabilizer's control mechanism on the bimodal flutter are demonstrated. Similar routings could be helpful when exploring the mechanism of other passive aerodynamic appendages. Highlights: Surface-Flutter-Derivatives are used to quantify the contributions of the deck's surface to the self-excited force. The wind-induced changes of the damping and frequency are allocated to different zones of the deck's surface. Numerical cases are conducted to investigate the control mechanism of stabilizer.